Take your time to grow: A field experiment on the hiring of youths in Germany - Dorothea Kübler; Julia Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
We investigate the effect of spells of no formal employment of young Germans on their chances of entering the labor market. We also study whether the potential negative effects of such spells can be mitigated by publicly provided training measures. In a field experiment, fictitious applications were sent to firms advertising an apprenticeship position for office manager. Our results show that applicants who have been out of school for two years are not less likely to be invited compared to applicants who apply during their last year of schooling. Among the two applicant types who have been out of school for two years, applicants who have taken part in a training course are significantly more likely to pass the first step in the recruitment process than those without supplementary schooling. Our findings can be explained with signaling and human capital theory while there is no evidence of stigma effects.
Keywords: J64; C93; 330; youth unemployment; hiring decisions; apprenticeships